Kv1.3 controls mitochondrial dynamics during cell cycle progression - Capera, J; Pérez-Verdaguer, M; Navarro-Pérez, M; Felipe, A (MDPI, 2021)
The voltage-gated potassium channel Kv1.3 is a potential therapeutic target for obesity and diabetes. The genetic ablation and pharmacological inhibition of Kv1.3 lead to a lean phenotype in rodents. The mechanism of regulation of body weight and energy homeostasis involves Kv1.3 expression in different organs, including white and brown adipose tissues. Here, we show that Kv1.3 promotes the proliferation of preadipocytes through the control of mitochondrial dynamics. Kv1.3 is expressed in mitochondria exhibiting high affinity for the perinuclear population. The mitochondrial network is highly dynamic during the cell cycle, showing continuous fusion-fission events. The formation of a hyperfused mitochondrial network at the G1/S phase of the cell cycle is dependent on Kv1.3 expression. Our results demonstrate that Kv1.3 promotes preadipocyte proliferation and differentiation by controlling mitochondrial membrane potential and mitochondrial dynamics at the G1 phase of the cell cycle.